Environmental Quality and Citizens’ Economic Well-Being - Correlations, Public Policies and Sustainability - Hămuraru , Maria; Buzdugan, Adriana (Acta Universitatis Danubius. Œconomica, 2025)
Objectives: This paper explores the relationship between environmental quality and perceived economic well-being in the Republic of Moldova, in light of increasing ecological pressures and concerns about sustainability. Prior Work: The study builds on established frameworks such as the Environmental Kuznets Curve (EKC) and ecological economics, and continues the authors’ earlier research on prosperity perceptions (Economic well-being and citizens’ perceptions of prosperity: a comparative analysis in the context of Moldova’s EU integration). The research is conducted within the project “Strengthening socio-economic and legal mechanisms to ensure the well-being and security of the citizens” (CONSEJ 01.05.02). These perspectives help clarify the interdependence between environmental integrity and socio-economic resilience. Approach: The paper draws on quantitative analysis of a 2024 sociological survey (n = 609), focusing on citizens’ perceptions of environmental quality, access to green spaces, and civic engagement. Results: Although citizens acknowledge the importance of environmental quality, satisfaction remains low-particularly regarding air quality and green infrastructure. Civic participation is limited. Implications: Findings support the need for inclusive, community-based environmental policies. Value: The study offers original insights into how environmental factors shape subjective well-being, informing sustainable development strategies.